The push-out bond strength of BIOfactor mineral trioxide aggregate, a novel root repair material - Makbule Bilge Akbulut; Durmus Alperen Bozkurt; Arslan Terlemez; Melek Akman (Restorative Dentistry & Endodontics)
ObjectivesThe aim of this in vitro study was to evaluate the push-out bond strength of a novel calcium silicate-based root repair material-BIOfactor MTA to root canal dentin in comparison with white MTA-Angelus (Angelus) and Biodentine (Septodont).Materials and MethodsThe coronal parts of 12 central incisors were removed and the roots were embedded in acrylic resin blocks. Midroot dentin of each sample was horizontally sectioned into 1.1 mm slices and 3 slices were obtained from each root. Three canal-like standardized holes having 1 mm in diameter were created parallel to the root canal on each dentin slice with a diamond bur. The holes were filled with MTA-Angelus, Biodentine, or BIOfactor MTA. Wet gauze was placed over the specimens and samples were stored in an incubator at 37°C for 7 days to allow complete setting. Then samples were subjected to the push-out test method using a universal test machine with the loading speed of 1 mm/min. Data was statistically analyzed using Friedman test and post hoc Wilcoxon signed rank test with Bonferroni correction.ResultsThere were no significant differences among the push-out bond strength values of MTA-Angelus, Biodentine, and BIOfactor MTA (p > 0.017). Most of the specimens exhibited cohesive failure in all groups, with the highest rate found in Biodentine group.ConclusionsBased on the results of this study, MTA-Angelus, Biodentine, and BIOfactor MTA showed similar resistances to the push-out testing.